(untitled) (Dhaka University Journal of Science, 2022)
Structural, electronic and optical properties of niobium doped ZnS are studied by using full-potential linearized augmented plane wave plus local orbital (FPLAPW+lo) method within the density functional theory (DFT). Computed results of Nb doped ZnS are compared with that of the pristine zinc blende. Tran-Blaha approach of modified Becke and Johnson local spin density approximation (TB-mBJ) is used to study electronic and optical properties. Estimated result shows that Nb reduces the bandgap of ZnS due to hybridization of Nb-4d orbital with S-3p orbital near the Fermi level. Niobium dopant provides half metallic nature to ZnS with 100% spin polarization. Maximum photo-response is noticed in the ultraviolet range for Zn1-xNbxS (x = 25, 12.5, 6.25 %). Highest peaks are shifted toward the lower energy range for higher dopant percentage. All these suggest that Nb doped ZnS solid solutions are suitable candidate for both energy filter of UV spectrum and spintronic device. Dhaka Univ. J. Sci. 69(3): 194-201, 2022 (June)